Specific Features of Legal Regulation of Local Taxes and Fees (Law and Safety, 2020)
It has been noted that the legal regulation of local taxes and fees is carried out simultaneously at the national and local levels. An exhaustive list of mandatory payments, the range of taxpayers, the objects of taxation, the maximum rate are defined at the national level. The powers granted by the state are used, each of the taxes and fees is established and put into effect separately, the collection mechanisms are regulated in details at the local level.The peculiarity of the legal regulation of local taxes and fees is that local self-government agencies do not have the right to set their own taxes and fees on their territory.It has been noted that each of the local taxes and fees has a number of its own features; examples of such features have been provided. The studied feature is the existence of a simplified system of taxation, accounting and reporting in Ukraine, in particular the legal mechanism for the administration of a single tax in Ukraine. The peculiarity of local taxation systems in Ukraine is its variability due to the instability of tax legislation.It has been concluded that local self-government agencies, taking into account the peculiarities of legal regulation of local taxes and fees, should focus on improving the efficiency of budget and tax planning through reasonable and prudent establishment of local taxes and fees in the relevant territorial community.The need to increase the share of local taxes and fees in local budget revenues has been stressed. It has been argued that most local taxes should be direct taxes to local budgets.
Keywords: a tax; tax system; taxation; local self-government agencies; local budgets; local taxes and fees; tax system reform